Spectral Analysis of ATP-Dependent Mechanical Vibrations in T Cells - Wohl, Ishay; Sherman, Eilon (Frontiers in Cell and Developmental Biology, 2021)
Mechanical vibrations affect multiple cell properties, including its diffusivity, entropy, internal content organization, and thus - function. Here, we used DIC and confocal microscopy to study mechanical vibrations in live (Jurkat) T cells. Vibrations were measured via the motion of intracellular particles and plasma membrane with and without ATP. We then used spectral analysis of these vibrations to distinguish the effects of thermal agitation, ATP-dependent mechanical work and cytoskeletal visco-elasticity. Parameters of spectral analyses could be related to mean square displacement (MSD) analyses with specific advantages in characterizing intracellular mechanical work. We identified two spectral ranges where mechanical work dominated vibrations of intracellular components: 0-3Hz for intracellular particles and the plasma-membrane, and 100-150Hz for the plasma-membrane. These vibrations of the cell membrane are expected to affect the formation and function of the immune synapse by effector cells. It may also facilitate immunological escape of extensively vibrating malignant cells.